Thermal stability of MAX phases - Low, It Meng; Pang, W. (Trans Tech Publications Ltd, 2014)
The susceptibility of MAX phases to thermal dissociation at 1300-1550 °C in high vacuum has been studied using in-situ neutron diffraction. Above 1400 °C, MAX phases decomposed to binary carbide (e.g. TiCx) or binary nitride (e.g. TiNx), primarily through the sublimation of A-elements such as Al or Si, which results in a porous surface layer of MXx being formed. Positive activation energies were determined for decomposed MAX phases with coarse pores but a negative activation energy when the pore size was less than 1.0 ìm. The insights for tailor-design of MAX phases with controlled thermal stability and intercalated MXenes for energy storage are addressed. © (2014) Trans Tech Publications, Switzerland.